(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the impact of the family environment on emotional development during adolescence. The psychological characteristics of adolescence, the role of the family psychological environment in the formation of personality, and its importance in the development of emotional stability are highlighted. The impact of positive and negative psychological environments in the family on the personality of adolescents is also analyzed based on the scientific views of psychologists.